Analisis Kegiatan Gemar Membaca Melalui Program Literasi Untuk Memperkuat Karakter Peserta Didik Di SDN 2 Socokangsi - Dzulfikar Aziz; Salma Raya Fitri; Melati Puspita; Nela Rofisian (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
This research aims to analyze reading activities through a literacy program in an effort to strengthen the character of students at SDN 2 Socokangsi. It is hoped that the literacy program implemented at this school can build students' interest in reading and form positive characters based on moral and social values. The method used in this research is a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the literacy program includes various activities such as reading for 10 minutes and literacy bills. It has succeeded in improving students' literacy skills and strengthening their character, especially in the aspects of discipline, responsibility and empathy. This program not only focuses on developing reading skills, but also on developing positive attitudes that support students' character growth. It is hoped that the results of this research can contribute to the development of literacy programs in other elementary schools as part of efforts to build national character through literacy-based education.